Belt and Road The First Decade. - Rogelja, Igor (Business with China., 2022)
China's Belt and Road Initiative (BRI) is one of the most talked about and little understood policy initiatives of China. This short book offers a comprehensive, balanced and policy-oriented analysis of the BRI and what it means for western businesses and polities.